A Women's Involvement in the Implementation of Source-Based Waste Management through Composting Method in Batuan Village, Gianyar-Bali - Muliarta I Nengah; Desak Ayu Diah Prawerti Desak Ayu Diah Prawerti; Kadek Somariana Kadek Somariana; Ketut Suwarmadi Putra Ketut Suwarmadi Putra; I Wayan Sudiarta I Wayan Sudiarta; Ni Luh Putu Putri Setianingsih Ni Luh Putu Putri Setianingsih (Asian Journal of Community Services, 2023)
Community service activities carried out in Batuan Village, Sukawati, Gianyar-Bali aim to improve the knowledge and skills of housewives in household waste management. Housewives have been leaders in waste management at the household level. The methods used include observation, interviews, socialization, and plot demonstration. Based on the results of interviews with 15 participants in composting training and plot demonstrations, it was found that 13% of housewives had routinely composted and 87% percent had never done composting, citing not knowing how to compost, not having a place for composting and reasons for time constraints. Housewives in Batuan Village after receiving socialization and training have a commitment to sorting waste and composting.